2004
DOI: 10.1002/eat.20022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the child and parent forms of the Questionnaire on Eating and Weight Patterns in the assessment of children's eating‐disordered behaviors

Abstract: Objective-The assessment of eating-disordered behaviors in middle childhood is challenging. Frequently, both child and parents are queried about the child's eating behavior. However, no direct comparisons between parent and child reports of child eating disturbance have been published. We compared results from the adolescent and parent versions of the Questionnaire on Eating and Weight Patterns (QEWP-A and QEWP-P, respectively) in a nontreatment sample of overweight and normal weight children.Method-The QEWP-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
42
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 33 publications
9
42
1
Order By: Relevance
“…The few studies addressing the agreement between parentally and child reported disordered eating found that there was little concordance when disordered eating behavior was actually present. 30,31 In addition, the degree to which younger children understand the concept of disturbed eating has generally been questioned. 32 On the other hand, Schur et al, 33 demonstrated that children of ages comparable to children in our study were well informed about dieting.…”
Section: Limitationsmentioning
confidence: 99%
“…The few studies addressing the agreement between parentally and child reported disordered eating found that there was little concordance when disordered eating behavior was actually present. 30,31 In addition, the degree to which younger children understand the concept of disturbed eating has generally been questioned. 32 On the other hand, Schur et al, 33 demonstrated that children of ages comparable to children in our study were well informed about dieting.…”
Section: Limitationsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] For example, when using the ChEDE, studies have found a 0% prevalence of BED 22,23 ; however, 7.9% of children aged 10-16 seeking outpatient weight loss treatment reported subthreshold binge eating 22 and of children aged 6-14, 6.2%, 3.1%, and 20.4% reported objective binge episodes, subjective binge episodes, and overeating, respectively. 23 When using the QEWP-A, although only 5.3% of children aged 6-10 met BED criteria, 33.1% reported loss of control over eating.…”
Section: Prevalence Of Bed In Childrenmentioning
confidence: 99%
“…However, it is also possible that the manifestations of binge eating in children may differ from those observed in adults, or that the questions asked on assessment measures of aberrant eating (which are often adapted for child use from adult forms) may not be readily understandable to children. To date, most studies have made use of single-item surveys, self-report questionnaires, parent-reports of their children's behaviors (Field et al, 1999;Morgan et al, 2002;Steinberg et al, 2004) and, only in a minority of cases, interview methodology . Comparisons of these investigations suggest that responses differ based upon the type of measure used and the particular respondent queried.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of these investigations suggest that responses differ based upon the type of measure used and the particular respondent queried. There is poor concordance in observed rates of binge eating when child self-reports are compared to parent-reports of children's behavior (Johnson, Grieve, Adams, & Sandy, 1999;Steinberg et al, 2004) or when child self-reports are compared to results of child interviews (Field, Taylor, Celio, & Colditz, 2004;Tanofsky-Kraff et al, 2003). Similarly, in studies using interview methodology, parent-reports of child binge eating have demonstrated poor concordance with child reports , adding to the confusion of what constitutes binge eating in children and whether a distinct syndrome exists during middle childhood.…”
Section: Introductionmentioning
confidence: 99%